LEGAL REVIEW OF MARRIAGE AGREEMENTS MADE POST-MARRIAGE AFTER THE APPROVAL OF MK DECISION NO. 69/PUU XIII / 2020 - Annisa Purba (Journal of Golden Generation Multidisciplinary, 2025)
The legal provisions governing the marriage contract according to the Republic of Indonesia Law No. 1 of 1974 and the Constitutional Court Decision No. 69/PUU-XIII/2015 can be carried out after marriage, because the meaning of Article 29 paragraph (1) of the Marriage Law is interpreted as long as the parties are bound. The agreement of both parties can submit a written agreement that is accepted by the contract drafter or notary. The Judge's opinion that the relevant application is stated in the Applicant's Marriage Agreement and the legal issues are also acceptable. The legal analysis of the permissibility of the marriage contract arises from the perspective of the law of the contract that the legal provisions of the marriage contract also bind third parties, so that the marriage contract must be registered with the Civil Service Secretariat or the Ministry of Religion. Because the MK decision as it is does not mean anything about registration, whether registration must be carried out immediately or wait for further registration/registration laws. Therefore, the legal consequences of a marriage contract can create legal guarantees for others.